Identification and in-silico characterization of Serpin genes in legumes genomes - MAINKAR, PAWAN S; L, MANOJ M; JAYASWAL, DEEPANSHU; AGARWAL, YAMINI; PRAJAPAT, RAKESH K; KANSAL, REKHA (The Indian Journal of Agricultural Sciences, 2020)
Serine protease inhibitors (serpins) are a unique family of protease inhibitor containing mobile reactive center loop. The availability of genome sequences of pigeonpea, soybean, commanbean, cowpea, mungbean and adzuki bean provided an opportunity to search for the serpin genes. A total of seven serpin genes were identified in the above legume genomes. Phylogenetic analysis of legume serpins, devided them into two major clades (Clade-I:VanSerpin, VraSerpin, VunSerpin, PvuSerpin and clade-II: GmaSerpin1, GmaSerpin2 and CcaSerpin) based on conserved reactive center (P2-P1’), domains and exon-intron boundary in the gene structure. The common reactive center of all the seven serpins indicated their ability to target cognate proteases and play an important role in response to insects, fungal pathogens and also the drought.